Fairness Preference of Preschoolers and the Effects of Family Background in China - Huang, Zhongjing; Shi, Lan; Wu, Jie (ECNU Review of Education, 2023)
Purpose This study investigates the fairness preference of five-year-old children in Shanghai, observing their distributive behaviors in both stakeholder and spectator games and showing how this behavior is linked to their family background. Design/Approach/Methods Participants had to make distributive choices in two experiments and distribute between themselves and another participant in the first choice. They had to distribute between two other participants in luck, merit, or efficiency situations in the second choice. Findings The results suggest that preschoolers showed a preference for splitting equally between themselves and another participant. The second choice showed a significant difference in fairness preference under a situation of luck between genders, and only children were more likely to accept an unequal allocation than those who had siblings. Originality/Value We believe that our study makes a significant contribution to the literature because it illustrates the variety of factors that can influence a child's fairness preference and fairness behavior and suggests when and how these aspects develop in children. Further, this is an original study exploring the fairness preference of preschoolers in Shanghai using an experimental economics method.